Evaluation of Physician Communication Skills During Simulated Vacuum-Assisted Deliveries [29M]. (May 2018) - Mella, Maria Teresa; Lee, Yuo-yu; Bernstein, Peter; Atallah, Fouad; O'Neill, Loraine; Friedman, Frederick
Abstract : INTRODUCTION: The objective of this study was to determine if a targeted education program using a mannequin-simulated vacuum-assisted delivery could improve the communication skills of obstetricians. METHODS: This study involved a concurrent assessment of the performance of obstetricians during vacuum-assisted vaginal deliveries using synthetic models. All obstetricians within an existing Obstetric Quality Improvement Collaborative with operative vaginal delivery privileges were enrolled in the study. All evaluators underwent a rigorous training program to ensure uniformity. Demographic information including years in practice and simulation experience were recorded. Eight communication skills and an overall assessment were scored using a standardized checklist. Performance on all variables was evaluated before and after a targeted training session. RESULTS: 288 obstetricians participated across the 5 study hospitals. The majority (69%) of subjects was female, and most (70%) had greater than 10 years of training. For all 8 communication skills measured and for the overall performance, there were statistically significant improvements following the simulation and targeted education session. Communication skills did not vary by sex of the participant. Obstetricians with an intermediate level of experience (6-10 years) appeared to perform best across all parameters. CONCLUSION: Our data show that a simulation training program including a targeted education session in vacuum assisted-deliveries improves obstetrician communication skills.